Fundamentals of track and field - Carr, Gerry (United States : Human Kinetics, 1999)
This edition teaches the basic skills for all track and field events, including a chapter devoted solely to race walking. Gerry Carr emphasizes learning the events in a series of progressions, from the most basic elements to the more advanced concepts
Keywords: Track--athletics